Chemical composition, antiradical, and enzyme inhibitory potential of essential oil obtained from aerial part of Centaurea pterocaula Trautv - ŞEN, ALİ; YILDIRIM, AYBENİZ; ŞENKARDEŞ, İSMAİL; BİTİŞ, LEYLA (TAYLOR & FRANCIS INC, 2021)
The chemical composition, free radical scavenging, alpha-amylase inhibitory, and 5-lipoxygenase inhibitory activity of the essential oil obtained from the aerial parts of Centaurea pterocaula Trautv. were examined. Twenty-nine compounds corresponding to 93.2% of the oil were identified in the oil of C. pterocaula. Hexadecanoic acid (13.9%), caryophyllene oxide (11.5%), spathulenol (11.4%), (E)-beta-damascenone (5.0%), hexahydrofarnesyl acetone (5.0%), and tetradecanoic acid (4.9%) were the main compounds of the oil. The oil exhibited good anti-inflammatory activity, inhibiting 5-lipoxygenase with an IC50 value of 86.22 mu g/mL. The oil was found to be active against DPPH radical and alpha-amylase with IC50 values of 83.05 and 79.66 mu g/mL respectively, while it showed moderate activity against ABTS radicals with IC50 value of 360.9 mu g/mL. To the best of our knowledge, this is first report on the chemical composition of C. pterocaula essential oil from Turkey; as well as on the biological activity of its essential oil.
Keywords: Centaurea pterocaula; essential oil composition; antidiabetic activity; anti-inflammatory activity; antioxidant activity; GROWING WILD; MEDICINAL-PLANTS; VOLATILE CONSTITUENTS; ANTIOXIDANT; EXTRACTS; ASTERACEAE; DC.; L.; ANTIMYCOBACTERIAL; COMPONENTS